Isolation of Mallory bodies and an attempt to demonstrate cell mediated immunity to Mallory body isolate in patients with alcoholic liver disease. Issue 9 (September 1981) - Gluud, C; Hardt, F; Aldershvile, J; Christoffersen, P; Lyon, H; Nielsen, J
Abstract : Mallory bodies were isolated from necropsy livers from patients with alcoholic hepatitis with and without cirrhosis with a Ficoll viscosity barrier. The purity of Mallory bodies in the isolate varied between 70 and 90%, estimated by counting Mallory bodies and non-Mallory body structures in haematoxylin-eosin stained smears. Electron microscopy confirmed the presence of Mallory bodies in the isolates. The Mallory body isolate was used as antigen in the agarose leucocyte migration inhibition test in order to test the cell-mediated immunity. No significant difference in leucocyte migration was found between controls and patients with alcoholic hepatitis, alcoholic steatosis, alcoholic cirrhosis and miscellaneous liver diseases.